2010
DOI: 10.1038/ki.2010.43
|View full text |Cite
|
Sign up to set email alerts
|

The Oxford IgA nephropathy clinicopathological classification is valid for children as well as adults

Abstract: To study the predictive value of biopsy lesions in IgA nephropathy in a range of patient ages we retrospectively analyzed the cohort that was used to derive a new classification system for IgA nephropathy. A total of 206 adults and 59 children with proteinuria over 0.5 g/24 h/1.73 m(2) and an eGFR of stage-3 or better were followed for a median of 69 months. At the time of biopsy, compared with adults children had a more frequent history of macroscopic hematuria, lower adjusted blood pressure, and higher eGFR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
112
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 181 publications
(123 citation statements)
references
References 18 publications
(19 reference statements)
6
112
0
5
Order By: Relevance
“…For each child, the SD score for MAP was calculated and used to normalize MAP to adult values. 29,30 MAP was calculated as 1/3 of the pulse pressure (systolic blood pressure-diastolic blood pressure) plus diastolic blood pressure. MAP was adjusted in children to .130/80 mmHg in case of an MAP SD score .1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For each child, the SD score for MAP was calculated and used to normalize MAP to adult values. 29,30 MAP was calculated as 1/3 of the pulse pressure (systolic blood pressure-diastolic blood pressure) plus diastolic blood pressure. MAP was adjusted in children to .130/80 mmHg in case of an MAP SD score .1.…”
Section: Methodsmentioning
confidence: 99%
“…MAP was adjusted in children to .130/80 mmHg in case of an MAP SD score .1. 29 The outcomes were the rate of renal function decline (slope of eGFR) and the combined outcome of a 50% reduction in renal function over time or ESRD, defined as eGFR,15 ml/min per 1.73 m 2 . We also addressed, as a surrogate outcome, the proportion of individuals with an initial proteinuria.1 g/d that achieved proteinuria,1 g/d during follow-up.…”
Section: Methodsmentioning
confidence: 99%
“…Extracapillary crescents are not included in the Classification because of their scarcity in the study population. In subsequent studies, the value of this histological classification has also been shown for pediatric IgAN patients [21], but to date it has not been evaluated in HSPN patients. Since the publication of the International Study of Kidney Disease in Children (ISKDC) classification [22], in HSPN, the percentage of crescents has been used for estimating disease severity and predicting outcome.…”
Section: Renal Biopsy Findingsmentioning
confidence: 99%
“…For example, when the predictive value of the Oxford classification system for IgA nephropathy was applied to children, there was inconsistent association of the pathologic criteria with renal outcomes (11)(12)(13)(14)(15). Therefore, we sought to validate this new pathologic classification of ANCA GN in cases with childhood onset and determine the association with renal outcomes.…”
Section: Introductionmentioning
confidence: 99%